SUHU, KELEMBABAN DAN INTENSITAS CAHAYA PADA PENANAMAN GREEN FOODER MENGGUNAKAN SISTEM SMART HIDROPONIK: Temperature, Humidity, and Light Intensity on Green Fooder Planting Using Smart Hydroponic System - Yuni Resti; Ratih Kemala Dewi; Tera Fit Rayani (IPB University, 2022)
This study aims to evaluate the use of smart hydroponic green fodder in controlling environmental factors (temperature, humidity, and light intensity) during green fodder production. Green fodder planting uses smart hydroponics with the help of sensors and Arduino systems to control the water irrigation system and environmental conditions such as temperature and humidity. The light source uses artificial light that comes from a 36-watt blue LED grow light. The data analysis is descriptive analysis. The data observed were daily temperature and humidity which were regulated using automatic sensors and manually observed using a thermometer as a control. The intensity of light was measured using a lux meter and observed using a spectrometer to measure the wavelength and intensity. The results showed that the environmental temperature during maintenance of green fodder ranged from 20.5°C-23.9°C with an average daily temperature of 22.7°C. Air humidity during maintenance of green fodder ranged from 51.1%-80.3% with an average of 69.5%. The intensity of light produced during maintenance ranged from 438.7 to 1,156.7 lux with an average of 656.6 lux. Based on the results of research, the use of smart hydroponic green fodder can create suitable environmental conditions for green fodder production as seen from the temperature, humidity, and light intensity that are suitable for hydroponic green fodder production. ABSTRAKPenelitian ini bertujuan untuk mengevaluasi penggunaan smart hydroponic green fodder dalam mengontrol factor lingkungan (suhu, kelembaban dan intensitas cayaha) selama pemeliharaan green fodder. Penanaman green fodder menggunakan smart hydoponic dengan bantuan sensor dan system Arduino untuk mengontrol system irigasi air dan kondisi lingkungan seperti suhu dan kelembaban. Sumber cahaya menggunakan cahaya buatan yang berasal dari lampu LED grow light 36 watt warna biru. Analisis data yang dilakukan adalah analisis deskriptif. Data yang diamati yaitu suhu dan kelembaban harian yang diatur menggunakan sensor otomatis dan diamati secara manual menggunakan termometer sebagai kontrol. Intensitas cahaya diukur dengan menggunakan lux meter dan diamati dengan menggunakan spektometer untuk mengukur panjang gelombang serta intensitasnya. Hasil penelitian menunjukan suhu lingkungan selama pemeliharaan green fodder berkisar antara 20,5 oC-23,9 oC dengan rata-rata suhu harian 22,7 oC. Kelembaban udara selama pemeliharaan green fodder berkisar antara 51,1%-80,3% dengan rata-rata 69,5%. Intensitas cahaya yang dihasilkan selama pemeliharaan berkisar 438,7-1.156,7 lux dengan rata-rata 656,6 lux. Berdasarkan hasil penelitian penggunaan smart hydroponic green fodder dapat menciptakan kondisi lingkungan yang sesuai untuk produksi green fodder terlihat dari suhu, kelembaban dan intensitas cahaya yang sesuai untuk pemeliharaan green fodder secara hidroponik.